Developing English educational videos for senior high school students - Afrilia, Lisa; Istikharoh, Lutfi (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2023)
The researcher developed English educational videos using The ADDIE Model as a part of Research and Development. Accordingly, this research objectives were to examine about self-production of English educational videos using the ADDIE model and the students’ perceptions of self-produced English educational videos in terms of appearance and content. The method used in this study was a mixed methodology. Meanwhile, the instruments to collect the data were expert validation sheets, questionnaires, and interview transcript guides to strengthen the data obtained from the questionnaire findings. The results of data assessment from an academic and technological expert’s validation indicated that the educational videos generated were characterized as very good, with a score of 91. The educational videos developed received an 80 score from an academic specialist. According to the expert validation results, the English educational videos created were good and could be used with a few revisions. Meanwhile, analysis data of 82.4 percent of 4th-semester students indicated that the English educational videos were very good. The perception of English educational videos among 12th-grade high school students was 95.2 percent which is classified as very good. Furthermore, the interview results bolstered an explanation for the video quality. The interview results also gave feedback and suggestions for improving, refining, and developing the produced English educational videos. Overall, the English educational videos developed using The ADDIE Model were of good-very good quality. With a few changes to increase the product’s quality, the English educational videos developed could be used as an English educational medium.